Revealing the quality of movement: A meta-analysis review to quantify the thresholds to pathological variability during standing and walking. (September 2016) - König, N.; Taylor, W.R.; Baumann, C.R.; Wenderoth, N.; Singh, N.B.
Highlights: ⿢ Meta-analysis of the thresholds between healthy and pathological task variability. ⿢ Results indicate an overall positive effect size of pathology on variability of 0.59 for walking and 0.8 for sway. ⿢ Upper thresholds of 2.6% CV stride time and 265 mm 2 sway area discriminated pathological from asymptomatic performance. ⿢ For CV of stride time and sway area, 1.1% and 62 mm 2 identified the lower thresholds for pathological variability. ⿢ An optimal window of healthy performance can aid in standardised monitoring of functional status in neurological cases. Abstract: Neuromotor processes are inherently noisy, which results in variability during movement and fluctuations in motor control. Although controversial, low levels of variability are traditionally considered healthy, while increased levels are thought to be pathological. This systematic review and meta-analysis of the literature investigates the thresholds between healthy and pathological task variability. After examining 13, 195 publications, 109 studies were included. Results from over 3000 healthy subjects and 2775 patients revealed an overall positive effect size of pathology on variability of 0.59 for walking and 0.80 for sway. For the coefficient of variation of stride time (ST) and sway area (SA), upper thresholds of 2.6% and 265 mm 2 discriminated pathological from asymptomatic performance, while 1.1% and 62 mm 2 identified the lower thresholds for pathological variability. This window of healthy performance now provides science based evidence for the discrimination of both extremely low and extremely high levels of variability in the identification as well as standardised monitoring of functional status in neurological cases.